Resistance and Resolution: Attentional Dynamics in Discourse. (12th February 2020) - Bledin, Justin; Rawlins, Kyle
Abstract: This paper centers on discourses where instead of accepting or rejecting an assertion, a hearer uses an epistemic possibility claim to bring a new subject matter to the original speaker's attention and consequently leads this speaker to change her mind and retract the initial claim. To analyze such resistance moves, we develop a new theory of attention-shift-induced belief change in which attention is modeled using granularity-levels or resolutions of logical space and refining a speaker's attention can allow her to combine more of her resolution-sensitive information and potentially change her beliefs. We integrate this theory into pre-existing machinery from the literature on formal models of discourse to account for both the informational and attentional dynamics in epistemic resistance discourses, and to lay out some of the formal prerequisites for a more comprehensive theory of resistance moves in general. Along the way, we introduce the new concept of a subject matter under public attention (SUP) and compare this with the more familiar concept of a question under discussion (QUD).